Posted In: KS3 , Year 11 maths
SHARE:

In maths, an equation is a statement that two things are equal. In an equation, there are two expressions, one on each side of the equal to sign.
The followings are examples of equations:
8 + 2 = 10
7 * 5 = 35
12 - 5 = 7
15 / 3 = 5

Variables in an equation

Variables are the unknown in an equation. An equation could contain one or more unknowns. In the equation 8 + x = 10, x is the unknown variable. We can now solve this equation to determine the value of x as shown below:
8 + x = 10
x = 10 - 8
Therefore, x = 2
This process of finding the value of the unknown is called solving the equation.

Practice questions
Question: Find the value of x in the following equations.
1. 12 - x = 7
2. 13 * x = 26
3. 5 + x = 8
( Answer: 5, 2, 3 )

Simultaneous equations
Simultaneous equations are two equations with two unknowns. They are called simultaneous equations because they must be solved together in order to determine the unknowns.
For example:
Given two simultaneous equations x + y = 10 and x - y = 6, find the values of x and y.
Equation 1: x + y = 10
Equation 2: x - y = 6
Add the two equations to eliminate the unknown y
2x = 16
x= 16/2 = 8
Now replace the value of x in equation 1
8 + y = 10
y= 10 - 8 = 2

Solving simultaneous equations using substitution

Sometimes you can use substitution to solve two simultaneous equations to determine the value of unknowns.
For example:
Given two simultaneous equations x + y = 12 and x = 2y, find the values of x and y.
Equation 1: x + y = 12
Equation 2: x = 2y
Replace the value of x in equation 1
2y + y = 12
3y = 12
y = 4
Now replace the value of y in equation x
x + 4 = 12
x = 8

Practice questions

Question: Find the value of x and y in the following equations: 3x + y = 7 and 3x - y = 5
( Answer:     Equation 1:     3x + y = 7
Equation 2:     3x - y = 5
6x = 12
x = 2
Replace the value of x in equation 1
3 * 2 + y = 7
6 + y = 7
y= 1
)

Question: Find the value of x and y in the following equations: y - 2x = 1 and 2y - 3x = 5
( Answer:     Equation 1: y - 2x = 1
Equation 2: 2y - 3x = 5
Rearrange equation 1: y = 1 + 2x
Substitute in equation 2: 2 (1 + 2x) - 3x = 5
2 + 4x - 3x = 5
2 + x = 5
x = 3
Use value of x in equation 1
y= 2 * 3 + 1 = 7
)

SHARE:

© Hozefa Arsiwala and teacherlookup.com, 2018-2019. Unauthorized use and/or duplication of this material without express and written permission from this site’s author and/or owner is strictly prohibited. Excerpts and links may be used, provided that full and clear credit is given to Hozefa Arsiwala and teacherlookup.com with appropriate and specific direction to the original content.